2021
DOI: 10.3390/ijerph18126384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PM2.5 Levels on Respiratory Pediatric ED Visits in a Semi-Urban Greek Peninsula

Abstract: Ambient air pollution accounts for an estimated 4.2 million deaths worldwide. Particulate matter (PM)2.5 particles are believed to be the most harmful, as when inhaled they can penetrate deep into the lungs. The aim of this study was to examine the relationship between PM2.5 daily air concentrations and pediatric emergency department (ED) visits for respiratory diseases in a Greek suburban area. All pediatric ED visits for asthma-, pneumonia- and upper respiratory infection (URI)-related complaints were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Some supporting evidence showed that among children hospitalized for pneumonia, positive associations were seen with short-term daily exposure to ambient air pollution [ 7 , 8 ]. Similarly, pediatric patient visits to the emergency department for respiratory symptoms were also increased in those with high levels of daily PM 2.5 exposure [ 9 ]. To date, the NAAQS of China has yet to set air pollutant standards to protect “sensitive subgroups”.…”
Section: Introductionmentioning
confidence: 99%
“…Some supporting evidence showed that among children hospitalized for pneumonia, positive associations were seen with short-term daily exposure to ambient air pollution [ 7 , 8 ]. Similarly, pediatric patient visits to the emergency department for respiratory symptoms were also increased in those with high levels of daily PM 2.5 exposure [ 9 ]. To date, the NAAQS of China has yet to set air pollutant standards to protect “sensitive subgroups”.…”
Section: Introductionmentioning
confidence: 99%
“…RRTIs are defined as a minimum of six to eight episodes per year, affecting 15%–20% of children under 5 years of age ( 2 ). The incidence of RRTIs has been increasing in recent years due to deterioration caused by environmental pollution and changes in lifestyle (e.g., early socialisation of children) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of researches results show that [1][2][3] , PM2.5 has great harm to human health, especially the respiratory system, heart disease and cardiovascular and cerebrovascular diseases. PM2.5 is one of the important factors that affect people's quality of life and human health.…”
Section: Introductionmentioning
confidence: 99%